GREEN GOVERNANCE: INTEGRATING ENVIRONMENTAL POLICY INTO PUBLIC DECISION-MAKING - Sarjito, Aris (Universitas Negeri Gorontalo, 2024)
This study delves into the multifaceted domain of Green Governance, aimed at integrating environmental policies into public decision-making processes. Grounded in qualitative research methods utilizing secondary data, the investigation unfolds key insights derived from various thematic domains. The exploration begins by uncovering the foundational elements crucial to Green Governance, unveiling key components and imperatives for effective environmental policy implementation. Stakeholder perspectives emerge as pivotal, shaping policy realities and influencing the trajectory of environmental initiatives. The study navigates through theoretical perspectives, shedding light on the intricacies of policy integration into public decision-making, drawing from diverse lenses such as the Advocacy Coalition Framework and Institutional Theory. Additionally, the research meticulously explores various governance models, dissecting collaborative and network-based approaches and elucidating their distinguishing features and comparative advantages in integrating environmental policies. Findings underscore the significance of collaboration, adaptive structures, stakeholder engagement, and inclusive decision-making in crafting effective green governance frameworks. Ultimately, this research culminates in a comprehensive understanding of Green Governance, providing insights vital for policymakers, practitioners, and stakeholders.